2023
DOI: 10.31351/vol31isssuppl.pp86-91
|View full text |Cite
|
Sign up to set email alerts
|

Determining the Prevalence of Upper and Lower Urinary Tract Infections’ Pathogens and Their Antibiotic Susceptibility Profile for Adult Patients in Al-Diwaniya, Iraq (Conference Paper) #

Abstract: Until today, one of the leading predominant infections is Urinary tract infection (UTI). It exerts a huge burden on health systems worldwide each year. Treating UTIs empirically with antimicrobials improves morbidity rates. This study aims to assess the prevalence of UTI-associated bacteria in adult patients and to determine their antibiotic susceptibility profile. A retrospective study was conducted for adult outpatients who visited Al-Diwaniya tertiary hospitals from January 2020 till February 2022 to review… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 37 publications
2
4
0
Order By: Relevance
“…This finding is concordant with several previously conducted studies in Iraq and Iran (Naqid et al, 2020, Vakilzadeh et al, 2020, Ibrahim et al, 2021, Alfetlawi and Jasim, 2022. This can be justified by an increased number of women being susceptibility to UTIs due to several factors including basic anatomy of shorter urethra, hormone fluctuations across the menstrual cycle, and genetic factors (Alfetlawi and Jasim, 2022). Catheterization was a HCA-APN risk factor when compared to CA-APN (P of < 0.01,OR 15.38,) and remained a potential risk factor in the multivariate analysis (P of 0.01, OR 8.52) (95 % CI 1.68-43.03).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This finding is concordant with several previously conducted studies in Iraq and Iran (Naqid et al, 2020, Vakilzadeh et al, 2020, Ibrahim et al, 2021, Alfetlawi and Jasim, 2022. This can be justified by an increased number of women being susceptibility to UTIs due to several factors including basic anatomy of shorter urethra, hormone fluctuations across the menstrual cycle, and genetic factors (Alfetlawi and Jasim, 2022). Catheterization was a HCA-APN risk factor when compared to CA-APN (P of < 0.01,OR 15.38,) and remained a potential risk factor in the multivariate analysis (P of 0.01, OR 8.52) (95 % CI 1.68-43.03).…”
Section: Discussionsupporting
confidence: 93%
“…In the present study, the frequency APN was higher among females, with 38 (90.5%) of CA-APN and 43 (78.2%) of HCA-APN cases occurring in female patients. This finding is concordant with several previously conducted studies in Iraq and Iran (Naqid et al, 2020, Vakilzadeh et al, 2020, Ibrahim et al, 2021, Alfetlawi and Jasim, 2022. This can be justified by an increased number of women being susceptibility to UTIs due to several factors including basic anatomy of shorter urethra, hormone fluctuations across the menstrual cycle, and genetic factors (Alfetlawi and Jasim, 2022).…”
Section: Discussionsupporting
confidence: 91%
“…The impact of the COVID-19 pandemic has led to changes in the field of epidemiology and the spread of numerous contagious infections, both in hospital and outpatient settings. AMR is a silent epidemic that gathered strength through the pandemic [ 18 ]. Many studies have analyzed the effect of the pandemic on AMR in the setting of UTI [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…AMR is a silent epidemic that gathered strength through the pandemic [ 18 ]. Many studies have analyzed the effect of the pandemic on AMR in the setting of UTI [ 18 ]. The reason behind this is multifactorial and is chiefly interconnected with the large amounts of antimicrobial agent consumption for prophylactic management or treatment of co- or secondary infections in COVID-19 patients [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Also, , another study showed that Staphylococcus spp. are the most common gram-positive pathogens causing UTIs [21] .…”
Section: Figure (4): Bacterial Isolates Of Uti In Pregnant Womenmentioning
confidence: 99%